Multiphase coupling mechanism of free surface vortex and the vibration-based sensing method. (1st February 2021) - Li, Lin; Tan, Dapeng; Wang, Tong; Yin, Zichao; Fan, Xinghua; Wang, Ronghui
Abstract: Multiphase vortex with free surfaces, as a common hydraulic phenomenon, occurs in many industrial processes such as metallurgy refining, chemical extraction, and hydropower station operation. Its internal real-time monitoring is of important significance to improve product quality and yielding rate, increase energy utilization rate, and achieve the safety and high-efficiency industrial production. However, the terrible physical conditions, including high temperature, limited space and surrounding interferences, always restrict the vortex flow field to be detected directly. Aiming at the matters, this paper presents a novel modelling and sensing method for multiphase vortex. Specifically, a mechanical dynamic model based on coupled level-set and volume-of-fluid (CLSVOF) method is set up to analyze the multiphase coupling mechanism. A Flügge equation-based displacement solving method is proposed to reveal the nonlinear vibration regularities. Then, a wavelet transform-based vibration sensing method is presented to identify the vortex critical penetration state. The simulated results show that the performed modelling and solving approaches of free surface vortex have better reveal the multiphase coupling mechanism and the nonlinear vibration characters. Initial disturbance and flow flux dominate the vortex forms and coupling intensities of multiphase coupling phenomenon respectively; the wavelet transform-based vibration sensing method can well recognize the transient distortion attribute. Highlights: A mechanical dynamic model is set up to analyze multiphase coupling mechanism. A Flügge equation-based method is presented to obtain the displacement response. Vortex vibration characters are revealed by the time-domain spectrum and cepstrum. A wavelet transform-based sensing method is called to identify distortion attribute.